Highly active and stable amorphous IrOx/CeO2 nanowires for acidic oxygen evolution. (15th December 2022) - Gou, Wangyan; Xia, Zhaoming; Tan, Xiaohe; Xue, Qingyu; Ye, Fan; Dai, Sheng; Zhang, Mingkai; Si, Rui; Zou, Yong; Ma, Yuanyuan; Ho, Johnny C.; Qu, Yongquan
Abstract: Development of highly active and durable electrocatalysts for acidic oxygen evolution reaction (OER) remains an unresolved grand challenge. Here, we reported the amorphous IrOx /CeO2 nanowires as highly active and acid-stable OER catalysts through a facile electro-spinning/calcination approach. The amorphous catalysts delivered a high mass activity of 167 A gIr −1 at 1.51 V, a low overpotential of 220 mV at 10 mA cm −2, and a stable performance for 300 h of continuous operation in acid. As revealed by complementary experimental and theoretical calculation results, the intimate nanoscale feature of IrOx /CeO2 creates abundant binary interfaces, at which CeO2 as an electron buffer regulates the adsorption of oxygen intermediates, lowers the activation barrier of OER, and suppresses the over-oxidation and dissolution of Ir, thereby significantly enhancing the OER activity and stability. This work provides a new strategy for designing highly active and acid-resistant OER catalysts. Graphical Abstract: Amorphous binary IrOx /CeO2 nanowires synthesized through a facile electro-spinning/calcination method delivered a highly active and stable performance for acidic oxygen evolution, where CeO2 as an electron buffer not only modulates the adsorption behavior of oxygen intermediates but also stabilizes the Ir oxidation states during the reaction to suppress the dissolution of iridium. ga1 Highlights: Synthesis of binary amorphous IrOx /CeO2 nanowires with abundant interfaces. High catalytic activity and stability of amorphous IrOx /CeO2 nanowires for acidic OER. CeO2 as an electron buffer to suppress the dissolution of Ir and reduce the activation barrier.